Material Politics: Utility Documents, Claims‐Making and Construction of the "Deserving Citizen" in Rio de Janeiro. (14th May 2020) - Pilo', Francesca
Abstract: Through an ethnographic study of a document in urban Brazil—the electricity bill—this article argues for developing a relational and materialist approach to citizenship. It analyzes the uses and meaning of this document for favela residents, the state, and the private electricity provider, within projects to regularize illegal connections and the so‐called "pacification" program, a state security policy to re‐establish state territorial control. It investigates the tensions between the market‐oriented processes of electricity regularization and citizenship by examining the implications of this contractual change on the way state and non‐state actors and residents frame rights and responsibilities linked to membership in society. Analysis of this document reveals how citizenship framing takes specific shape in line with both state reforms and urban processes of differentiation. It shows that the bill both materializes normative ideas of "deserving citizenship" as a territorial, moral, and material process, and realizes the potential for political contestation. The article thus expands on analysis of documents as material mediators of social and political relations and proposes an understanding of citizenship as a negotiated process involving people, state, and non‐state actors and objects.